Relationship of Emotional Intelligence with Social Anxiety and Social Competence of Adolescents - Inam, Attiya; Khalil, Hafsa; Tahir, Warda Binte; Abiodullah, Muhammad (Nurture, 2014)
This study was an effort to find out the relationship of emotional intelligence with social anxiety and social competence of adolescents. The study was carried out at Ibne Sina College and SICAS. A sample of 130 adolescents between the ages of 14-16 years was randomly selected. Emotional quotient inventory youth version (EQi- YV) by Baron, Kutcher Social Anxiety Disorder Scale for Adolescents (K-GSADS-A) and Measures of Adolescence Social Performance (MASP) were used to find out the emotional intelligence, social anxiety and social competence respectively. Data was analyzed using descriptive statistics as well as independent samples t-test, ANOVA and Pearson correlation coefficient. Results showed that girls experience more social anxiety as compared to boys. Further analysis revealed a negative correlation between emotional intelligence and social anxiety, a positive relation between emotional intelligence and social competence and a negative relation between social anxiety and social competence of both boys and girls.